Risk of VTE associated with PORTs and PICCs in cancer patients: a systematic review and meta-analysis - Wang, Pengpeng; Soh, Kim Lam; Ying, Yanping; Liu, Yuanhang; Huang, Xueling; Huang, Jinlan (Elsevier BV, 2022)
Background: Totally implantable venous access ports (PORTs) and peripherally inserted central catheters (PICCs) are associated with an increased risk of venous thromboembolism (VTE). It is not known which type of catheter is most at risk of thrombosis. Objective: We aimed to study the incidence of PORT-related VTE and PICC-related VTE in cancer patients by a meta-analysis. Methods: A systematic search was performed using PubMed, Embase, Web of Science and the Cochrane Library. Cohort studies and randomized controlled trials (RCTs) comparing PORT-related VTE and PICC-related VTE in cancer patients were included. Quality was assessed using the Cochrane Collaboration tool for RCTs and the Newcastle-Ottawa Scale (NOS) for cohort studies. Random-effects meta-analysis was used to calculate odd ratio (OR). Sensitivity and subgroup analyses were conducted. Results: In total, 22 studies comprising 11,940 patients were retrieved. Our meta-analysis of 22 studies suggested that the risk of PORT-related VTE was lower than that of PICC-related VTE in cancer patients (OR = 0.38, 95% CI: 0.25–0.58). The subgroup analysis showed that the risk of PORT-related VTE and PICC-related VTE is different in different regions. In the non-Asian countries, PORTs were associated with a decreased risk of VTE compared with PICCs. (OR = 0.41, 95%CI: 0.27–0.61). However, there was no significant difference in the risk of PORT-related VTE and PICC-related VTE in the Asian countries (OR = 0.23, 95% CI: 0.05–1.12). Conclusions: PORTs are associated with a lower risk of VTE than PICCs in cancer patients. The risk of VTE and benefits should be considered when selecting PORTs or PICCs for cancer patients.